POSTCOLONIAL PERSPECTIVES ON MALAY BATU BARA ORAL NARRATIVES: INSIGHTS FROM ENGLISH LITERARY THEORY - Efrizah, Doni (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study investigates how Malay Batu Bara oral narratives express cultural identity, morality, and resistance through the analytical lens of English postcolonial theory. Addressing the lack of research applying postcolonial literary frameworks to Indonesian oral traditions, the study aims to reinterpret local oral texts using key concepts from Bhabha (hybridity, mimicry) and Spivak (subaltern voice) to understand how these narratives negotiate cultural power. A qualitative comparative design was employed, drawing on twelve Batu Bara oral texts including pantun, gurindam, ritual verses, and folktale fragments supplemented by interviews with five cultural informants. These were compared with selected English literary works exhibiting parallel moral themes. Data were analyzed using thematic coding and cultural semiotics to identify symbolic patterns and interpret how postcolonial concepts function within the local narratives. Findings indicate four specific moral and cultural patterns recurring across the oral texts: ecological harmony, respect for social hierarchy, communal ethics, and moral sincerity. These values are articulated through metaphor, performance, and collective expression, revealing how Batu Bara narratives function as moral counter-discourses that embody subaltern agency and cultural resilience. The cross-analysis demonstrates a form of “moral hybridity,” where local ethical worldviews intersect with and reinterpret English postcolonial concepts. The study contributes theoretically by positioning Malay oral literature as an active epistemological space within postcolonial discourse and practically by offering a model for integrating indigenous oral traditions into comparative literary pedagogy.